Fluoride in drinking water and other factors associated with the prevalence of fluorosis in children from 10 to 12 years of The Canton Colta Chimborazo province - Yautibug Balla, Esther (2017)
Objective: Determine the prevalence of fluorosis in children of 10 to 12 years of the canton Colta Province Chimborazo and relate its presence with the percentage of fluorine present in drinking water and other associated factors. Materials and Methods: An epidemiological, observational and descriptive study was conducted with a sample of 219 children enrolled in the canton's educational units, which met the pre-established inclusion and exclusion criteria. They were evaluated by visual clinical examination with photographic record of their upper and lower anterior teeth. The photographs obtained were analyzed by three persons qualified and calibrated in the detection of fluorosis index TF (Thylstrup & Fejerskov). Applied to the parents of the children a previously validated survey. Results: The results showed a prevalence of fluorosis grade 2 and grade 3, 36% and 29% respectively. It found a direct relationship between the consumption of packaged beverages, intake of dentifric